Spiritual health: conceptual, philosophical and practical aspect of iman restoration theraphy - Abdul Razak, Abdul Latif (IIUM Press, International Islamic University Malaysia, 2019)
Spiritual Health: Conceptual, Philosophical and Practical Aspects of Iman Restoration Theraphy illustrates in detail about Iman Restoration Theraphy (IRT), a new psychotherapeutics approach which is based on the study of the Qur'an, Sunnah and the works of early Muslim scholars. IRT has come to restore in man his true spiritual human nature and upholds the platform that human spirituality is a major factor in man's psychological and mental problems. Its main foundation is Iman (faith) which is the first fundamental principle among the pillars of Islam and what makes a Muslim a true servant of Allah (SWT). The raison d'etre of this book is to make the readers know the causes of their psycho-spiritual problems and be able to fix the problems themelves. The book is being presented in a simple way with simple language that makes it readable by readers from different background even to readers with n basic psychology, counseling and psychotheraphy. For the experts and professionals in the field of counseling, psychotheraphy and even motivations, this book provides very important inputs to ensure the sustainable positive improvements happen to the clients. It nutures a deep, strong and healthy root that produces a tree with strong branches against all challenges of life.